The Rate of Increase in the Delivery of Blood Components to Medical Organizations in Kazakhstan for 8 Years - Massalimova, Alua (Asian Journal of Pharmaceutics (AJP), 2018)
Background and Objectives: To study the rate of increase and volume of blood components delivered to medical organizations in Kazakhstan for the years 2008–2015. Materials and Methods: The work used statistical sources for monitoring the activity of the blood service of Kazakhstan. The methods used for processing the obtained data were dynamics activity indexes, indicators of intensity of dynamics, and direct ranging. Results: The period from 2008 to 2015 saw an increase in the volume of blood components passed to medical organizations per 1000 persons: The growth rate of platelet concentrate in 2015 was +21.5, erythrocyte-containing media was +0.7, and plasma was −2.3. In the 2008–2015 period, the specific weight of leukoreduced blood components at the output to medical organizations increased the growth rate of platelet concentrate in 2015 was +1.1, erythrocyte-containing media +4, and plasma +11.8. In 2015, the specific weight of leukoreduced blood components was platelet concentrate - 95.0%, erythrocytes - 68.0%, and plasma - 28.4%. In 2015, the production of erythrocytes in Kazakhstan per 1000 persons was 10.0, platelets - 2.05 and plasma 8.9. Conclusions: Over the period of 2008–2015, the volume of blood components issued to medical organizations per 1000 persons increased, with an increase in platelet concentrate of 1.4 times. In 2015, the growth rate, compared to the previous year, was −2.3; the rate of increase in platelet concentrate was 21.5, erythrocyte-containing media increased 5.9 times with a rate of increase of 0.7 and plasma increased 3.6 times. The period of 2008–2015, the specific gravity of the leukoreduced blood components issued to medical organizations increased the platelet concentrate by 67.9 times. In 2015, the rate of platelet concentrate increase was 1.1, the erythrocyte-containing media increased 7.5 times with a rate of increase of 4.4, and plasma increased 3.8 times with a rate of growth of 11.8. Managerial decisions are necessary; it is necessary to make managerial decisions to increase the specific gravity of plasma leukoreduction. In Kazakhstan, the production of erythrocytes per 1000 persons in 2015 was 10.0, platelets - 2.05 and plasma - 8.9.